Acetylcholine-Induced Translocation of RhoA in Freshly Isolated Single Smooth Muscle Cells of Rat Bronchi - Yoshihiko Chiba; Tetsuro Uchida; Hiroyasu Sakai; Teruaki Oku; Saotomo Itoh; Tsutomu Tsuji; Miwa Misawa (Elsevier, 2004)
By using immunofluorostaining and confocal laser microscopy, acetylcholine-induced translocation of RhoA was visualized in freshly isolated bronchial smooth muscle cells of the rat. The cellular distribution of RhoA at rest was observed uniformly in the cytosolic space with no staining in the nucleus, whereas acetylcholine stimulation induced a relocalization of RhoA to the cell periphery. From the results of line scans and surface plots, the peripheral to cytosolic ratio of RhoA was significantly increased by acetylcholine stimulation. Thus, the present study clearly demonstrated an acetylcholine-induced translocation of RhoA to the plasma membrane in single bronchial smooth muscle cells of the rat. Keywords:: bronchial smooth muscle cell, RhoA translocation, Ca2+ sensitization